Softmobility/Cybermobility New Urban Activities and Digital Mobility - Fistola, Romano (TeMA - Journal of Land Use, Mobility and Environment, 2008)
The potential of substituting the physical transfer by using telecommunication was suggested already at the end of the 19th century. Replacing the physical transfer with a telematics flow, moving the bits and not the atoms (Mitchell, 1995), can be considered a form of “sustainable mobility” that does not produce strong impacts on the urban physical system. The cybermobility can be therefore considered as a form of soft mobility which allows a virtual transfer in order to reach an urban activity for a specific service (administrative, training, business, tourist, information one etc.). Unfortunately the several studies on this subject do not confirm the replacing effect. This paper suggests the overturn of the thought by using an approach which chiefly considers the city activities (functions) and their power of acftracting the flows of mobility inside the urban system. In particular, it should be considered the possibility that those functions could undergo a process of “virtualization” thanks to the spreading of new technologies in the way through which citizens use the city. The possibility of working out procedures capable of quantifying the modifications produced and calculating the (real and/or potential) values of transformation on the territory offers new opportunities of governing also the “invisible” transformations generated by the spreading of net-society.